Ameliorative Effects of Antibiotic-, Probiotic- and Phytobiotic-Supplemented Diets on the Performance, Intestinal Health, Carcass Traits, and Meat Quality of Clostridium perfringens-Infected Broilers - Hussein, Elsayed O.S. (Animals (Basel), 2020)
SIMPLE SUMMARY: Necrotic enteritis is considered the most important economic problem for the poultry industry due to the sudden death rates of up to 50%. However, there is limited information concerning the ameliorative role of probiotic and/or phytobiotic compounds in the prevention of Clostridium perfringens infections in broilers. Hence, this trial is conducted to evaluate the influence of some antibiotic, probiotic and phytobiotic compounds (Maxus, CloStat, Sangrovit Extra, CloStat + Sangrovit Extra, and Gallipro Tect) on the growth performance, carcass traits, intestinal health, and meat quality of broiler chicks. The obtained in vivo results highlight that a probiotic- and/or phytobiotic-supplemented diet has many positive effects on the performance, organ weight, and meat quality of broilers. Besides, a notable reduction in the lesion score is observed with a combined probiotic and phytobiotic diet. ABSTRACT: The poultry industry needs efficient antibiotic alternatives to prevent necrotic enteritis (NE) infections. Here, we evaluate the effects of probiotic and/or prebiotic dietary supplementation on performance, meat quality and carcass traits, using only an NE coinfection model, in broiler chickens. Three hundred and twenty-four healthy Ross 308 broiler chicks are allocated into six groups. Taking a 35 d feeding trial, the chicks are fed a basal diet with 0.0, 0.1, 0.5, 0.12, 0.5 + 0.12, and 0.2 g Kg(−1) for the control (T(1)), Avilamycin (Maxus; T(2)), live probiotic (CloStat (Bacillus subtilis);T(3)), natural phytobiotic compounds (Sangrovit Extra (sanguinarine and protopine); T(4)), CloStat + Sangrovit Extra (T(5)), and spore probiotic strain (Gallipro Tect (Bacillus subtilis spores); T(6)) treatments, respectively. Occurring at 15 days-old, chicks are inoculated with Clostridium perfringens. The obtained results reveal that all feed additives improve the performance, feed efficiency, and survival rate, and reduces the intestinal lesions score compared with the control group. The T(6) followed by T(3) groups show a significant (p < 0.05) increase in some carcass traits, such as dressing, spleen, and thymus percentages compared with other treatments. Also, T(5) and T(6) have significantly recorded the lowest temperature and pHu values and the highest hardness and chewiness texture values compared to the other treated groups. To conclude, probiotics combined with prebiotic supplementation improves the growth, meat quality, carcass characterization and survival rate of NE-infected broiler chickens by modulating gut health conditions and decreasing lesion scores. Moreover, it could be useful as an ameliorated NE disease alternative to antibiotics in C. perfringens coinfected poultry.